Phage (cocktail)-antibiotic synergism: a new frontier in addressing Klebsiella pneumoniae resistance - Chandrasekar Karthika; Nambiraman Malligarjunan; Nagaiah Hari Prasath; Shunmugiah Karutha Pandian; Shanmugaraj Gowrishankar (Frontiers in Microbiology)
Phages, which play a crucial role in regulating bacterial populations and evolution, have gained renewed attention as potential therapeutic agents especially in the face of rising antimicrobial resistance, such as in Klebsiella pneumoniae– a MDR pathogen with significant clinical implications for immunocompromised individuals. In this milieu, the present investigation aimed at evaluating the therapeutic potential of two lytic phages, KPKp (jumbo phage) and KSKp, as potential candidates for phage treatment. Initial purification and TEM characterization revealed their family as Ackermannviridae (KPKp) and Straboviridae (KSKp). The one-step growth curve analysis divulged that KPKp and KSKp exhibit burst sizes of ~98 and ~121 and latency periods of 8 and 12 min, respectively. Genomic analysis unveiled linear double-stranded DNA as their genome with sizes 206,819 bp (KPKp) and 167,101 bp (KSKp) lacking virulence or lysogenic genes, signifying their therapeutic suitability. Evaluation of phages as a cocktail demonstrated a substantial improvement in lytic ability, achieving complete (100%) lysis (at MOI 1) of clinical isolates compared to individual phages, achieving 50 and 25% lysis at MOI 1. In vitro investigations demonstrated that the phage cocktail significantly decreased both planktonic and sessile cells. Additionally, the phage (cocktail)-antibiotic synergism (PAS) achieves over 90% inhibition of K. pneumoniae, even at sub-lethal antibiotic doses. PAS treatment significantly prolongs the lifespan of K. pneumoniae-infected Galleria mellonella. Compared to cocktail phage therapy, PAS demonstrates a superior reduction in bacterial load. In conclusion, the combination of phages and antibiotic holds potential for addressing clinical challenges associated with MDR K. pneumoniae infection.